Correlation of Mastoid Pneumatization with Middle Ear Pathology in Unilateral Squamous Type of Chronic Otitis Media - Bhandari, Shama; Paudel, Dhundi Raj; Mahaseth, Subhash Chandra (Journal of Nepalgunj Medical College, 2022)
Introduction: Chronic otitis media is chronic inflammation of middle ear cleft followed by permanent abnormality of tympanic membrane. As mastoid a part of temporal bone is in close relation to middle ear; its pneumatization plays an important role in pathogenesis and prognosis of chronic otitis media. Aims: To study the pneumatization pattern of mastoid in unilateral chronic otitis media and its relationship with contralateral mastoid, diseased side tympanic membrane and ossicular status. Methods: Forty patients of 10-65 year of age diagnosed as unilateral chronic otitis media squamous type were selected. They were otoscopically evaluated for retraction and perforation of tympanic membrane and were subjected to high-resolution computed tomography of temporal bone. High resolution computed tomographies were analyzed for mastoid status of bilateral ear and ossicular involvement. During mastoidectomy ossicular status was noted and correlated with high resolution computed tomography. Results: Forty cases were enrolled in the study. Age ranged from10-65 years. On radiological analysis of temporal bones, 21(52.5%) mastoids were sclerotic, 15(37.5 %) mastoid diploic and 4(10%) were pneumatized in the diseased sides. Contralateral side showed pneumatization in 23(57.5%), diploic in 11(27.5%) and sclerotic in 6(15%) Amongst 21 sclerotic mastoid, 11(52.3%) patient had retraction in pars tensa and 9(42.8 %) had retraction of pars flaccida. In total 15 diploic mastoids retraction of pars tensa was in 8(53.3%) and pars flaccid retraction in 8(53.3%) All three ossicles were involved in 8(38%), Malleus and incus were eroded in 3(14%), incus were eroded in 7(33.3%), malleus were eroded in 3(14%) and ossicles were intact in 3(14%)of 21 sclerosed mastoids on high resolution computed tomography. In remaining 19 non sclerotic mastoids all 3 ossicles were eroded in 4 (21%), malleus plus incus eroded in 8 (16%), incus were eroded in 5(26.3%) andossicular chain was intact in 2(10%). Conclusion: Mastoid pneumatization pattern not only effect to the pressure of middle ear leading to chronic otitis media but also alter the pathogenesis and outcome of chronicotitismedia. Contralateral mastoid pneumatization is not altered in unilateral Chronic otitis media.